Thiophene and its sulfur inhibit indenoindenodibenzothiophene diradicals from low-energy lying thermal triplets. Issue 11 (November 2018) - Dressler, Justin; Teraoka, Mitsuru; Espejo, Guzmán; Kishi, Ryohei; Takamuku, Shota; Gómez-García, Carlos; Zakharov, Lev; Nakano, Masayoshi; Casado, Juan; Haley, Michael
Abstract Many qualitative structure–property correlations between diradical character and emerging molecular properties are known. For example, the increase of diradical character further decreases the singlet–triplet energy gap. Here we show that inclusion of thiophenes within a quinoidal polycyclic hydrocarbon imparts appreciable diradical character yet retains the large singlet–triplet energy gap, a phenomenon that has no precedent in the literature. The low aromatic character of thiophene and its electron-rich nature are the key properties leading to these unique findings. A new indenoindenodibenzothiophene scaffold has been prepared and fully characterized by several spectroscopies, magnetic measurements, solid-state X-ray and state-of-the-art quantum chemical calculations, all corroborating this unique dichotomy between the diradical input and the emerging magnetic properties. New structure–property relationships such as these are not only extremely important in the field of diradical chemistry and organic electronics, but also provide new insights into the versatility of π-electron chemical bonding. A paradoxical case of a well-defined diradicaloid that has an unusually large singlet–triplet energy gap (ΔES-T ) imparted by the thiophene sulfur atom is reported. Quantum chemistry, organic synthesis, molecular spectroscopies, X-ray crystal analysis and high-temperature magnetic measurements help account for the dichotomy between the large diradical character and large ΔEST .